Cardiovascular Effects of a Glycosylated Flavonoids-Rich Leaf Extract from Brazilian Erythroxylum campestre: A Potential Health Bio-Input - Letícia Henrique Dantas Gomes de Lima; Marcos Willian Francelino Gomes; Thays Siqueira de Sá Curado; Lara Marques Naves; Stefanne Madalena Marques; Marilene Silva Oliveira; John Ihayi Ogbu; Antonio Carlos Severo Menezes; Giuliana Muniz Vila Verde; James Oluwagbamigbe Fajemiroye; Gustavo Rodrigues Pedrino (Pharmaceuticals)
Background: Bioactivity assessments of plant-derived products can benefit human and animal health, especially in regions with vast plant diversity. This study focused on chemical and cardiovascular analyses of Erythroxylum campestre A. St. Hil. leaf extracts. Methods: High-performance liquid chromatography, liquid chromatography coupled with mass spectrometry, and nuclear magnetic resonance spectroscopy were used to elucidate the structures of the flavonoids in E. campestre. The E. campestre methanolic fraction (ECM-ppt-M; at doses of 1, 2, 3, and 6 mg∙kg−1 or vehicle) was administered intravenously to normotensive and spontaneously hypertensive rats (SHRs), and we recorded the mean arterial pressure (MAP), heart rate (HR), renal vascular resistance (RVR), and aortic vascular resistance (AVC). Results: The ECM-ppt-M extract demonstrated significant antihypertensive activity, as evidenced by reductions in MAP, RVR, and AVR, with effects that were particularly pronounced in SHRs. Following the establishment of these cardiovascular effects, phytochemical analysis revealed the presence of glycosylated flavonoids, which are likely contributors to the observed antihypertensive properties of the extract. Conclusions: The notable reductions in MAP and vascular resistance observed with ECM-ppt-M treatment suggest its antihypertensive effect. These findings demonstrate the potential therapeutic value of this extract with regard to the treatment of hypertension. Future studies on ECM may provide a promising therapeutic alternative capable of reducing the risk of toxicity and adverse effects associated with synthetic drugs.